Design, Synthesis, and Characterization of Novel Coordination Compounds of Benzimidazole Derivatives with Cadmium - Anita Raducka; Marcin Świątkowski; Izabela Korona-Głowniak; Barbara Kaproń; Tomasz Plech; Małgorzata Szczesio; Katarzyna Gobis; Agnieszka Czylkowska (MDPI AG, 2022)
Four complexes of Cd(II) with benzimidazole derivatives were synthesized and named C1, C2, C3, and C4. All coordination compounds were characterized through elemental analysis (EA), flame atomic absorption spectrometry (FAAS), Fourier-transform infrared spectroscopy (FTIR), thermogravimetric analysis coupled with mass spectrometry) (TG-MS), a cytotoxicity assay (MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazoliumbromide)), and computational chemical analysis for absorption, distribution, metabolism, and excretion (ADME). All of the obtained results are compatible and are consistent with the respective structures of the obtained compounds and their properties. The various techniques used allowed the determination of the composition, proposed structure of the compounds, their thermal stability and thermal properties, and the method of coordination between the metal (II) ion and the ligand. The ADME technique was also used to estimate the physicochemical and biological properties. The antitumor activity of the compounds was determined with an MTT assay on the glioblastoma (T98G), neuroblastoma (SK-N-AS), and lung adenocarcinoma (A549) cell lines, as well as normal human skin fibroblasts (CCD-1059Sk). Compound C2 was found to have potential antitumor properties and to be effective in inhibiting the growth of neuroblastoma cells. The antimicrobial activity of Cd complexes, free ligands, and reference drugs was tested against six strains of Gram-positive bacteria, five strains of Gram-negative rods, and three strains of yeasts. Compound C3 significantly increased activity against Gram-positive bacteria in comparison to the ligand.